Narrative perspectives in selected Ghanaian Hiplife lyrics - Samuel Kwesi Nkansah (Cogent Arts & Humanities)
Since the emergence of Hiplife as a musical genre in Ghana, it has enjoyed some scholarly attention, focusing primarily on issues pertaining to its evolution as a blend of Hip hop and Ghanaian Highlife genres, as well as how it employs linguistic resources involving code-switching and proverbs to comment on social issues. In this study, I approach the Ghanaian Hiplife genre from a stylistic perspective by focusing on the narrative perspectives Ghanaian Hiplife artistes use in conveying their messages to listeners. From the analysis, it was found that the artistes, in most cases, adopted the autobiographical, third-person and multi-perspectival narrative approaches where the narrator combined either the first-person or the third-person narrative technique. Also, the artistes used multimedia approaches, dialogue, cantor-response, and apostrophes in the songs. The study concludes that Hiplife artistes use traditional narrative perspectives as the initial tools and then adopt other narrative perspectives to be innovative, kill boredom and have lasting stylistic effects on listeners. The study provides a window for literary scholars to be more open to approaching literary analysis as modern creativity transcends the traditional purviews of point of view into more adoptive modes for stylistic effects.